A laser welding bushing applied to an automobile oil pump and a preparation method thereof
Patent Information
- Application Number
- CN202611053962.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-15
- Publication Date
- 2026-10-20
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of self-lubricating material manufacturing technology, and in particular to a laser-welded bushing for use in automotive oil pumps and its preparation method. Background Technology
[0002] Fuel pumps in gasoline vehicles, especially high-pressure fuel pumps, are core components of the automotive powertrain, enduring high pressure, friction, corrosion, and vibration over extended periods. A bushing is installed on the output shaft of each fuel pump. This bushing typically consists of a sleeve and a gasket. Both the sleeve and gasket are made of the same composite material, making the choice of this composite material crucial. The composite material usually consists of a base layer and a lubricating layer; the base layer can be made of copper alloy, while the lubricating layer is made of PTFE. Due to the demands of fuel pump operation, the gasket cannot have gaps, so it must be punched from a single piece of composite material and then welded to the rolled sleeve. However, the welds used in fuel pumps require precise assembly and gap control, as the fit between the internal plunger and the bushing is critical to fuel supply efficiency. Therefore, extremely high assembly precision must be ensured during welding. For high-pressure fuel pumps, the assembly precision requirements for their core components are even higher, sometimes reaching one-seventieth the diameter of a human hair. The rotational accuracy of the bushing must also be controlled within 0.02 mm to ensure stable and reliable product performance. Furthermore, the mating clearance between the plunger and the bushing must be strictly controlled within the range of 0.002mm to 0.009mm. If the fit between the sealing ring and the plunger is involved, the interference fit must be controlled between 0.03mm and 0.15mm to ensure sealing reliability while reducing wear. Due to these high precision requirements, laser welding is now often used to weld the sleeve and gasket.
[0003] The laser beam emitted during laser welding consists of high-energy photons, with extremely high energy density at its focal point, generating plasma temperatures reaching 10,000°C to 20,000°C or even higher. Naturally, different substrate layers require different temperatures. Furthermore, during laser welding, the beam is focused on an extremely small area, down to the micrometer level. This is the primary reason for using laser welding, as the tiny welding area ensures precision, and the bushing itself is relatively thin. However, because the heat is extremely concentrated, melting metal instantly, and the heat-affected zone is very small, the requirements for the lubricating layer on the non-welding side are extremely high. When using plastic materials such as PTFE, the high temperatures during laser welding can easily damage this lubricating layer, causing blistering, creep, deformation, or even perforation, leading to reduced product yield and increased product costs. Summary of the Invention
[0004] In view of this, the present invention provides a laser-welded bushing for use in automotive oil pumps and a method for preparing the same, in order to solve the above problems.
[0005] A laser-welded bushing for an automotive oil pump comprises a sleeve and a gasket. The gasket is laser-welded to one axial end of the sleeve. Both the sleeve and the gasket are made of a composite material. The composite material includes a substrate layer and a self-lubricating layer disposed on the substrate layer. The self-lubricating layer is composed of modified PTFE, metal or metal oxide, carbon fiber, silica, graphite, and glass fiber. By weight percentage, the modified PTFE content is 40%–75%, the carbon fiber content is 10%–20%, the silica content is 2%–5%, the graphite content is 5%–15%, the glass fiber content is 5%–25%, and the metal or metal oxide content is 2%–40%. The modified PTFE is prepared by modifying the PTFE with a modified perfluorinated modifier, which is prepared by modifying the perfluorinated modifier with octafluorocyclobutane or functionalized fullerene.
[0006] Furthermore, the substrate layer is made of a metallic material, which may be a copper alloy or a steel plate.
[0007] Furthermore, the copper alloy is one of tin bronze, lead bronze, and aluminum bronze.
[0008] Furthermore, the perchloric modifier is perfluoropropyl vinyl ether or perfluoron-propyl vinyl ether.
[0009] Furthermore, the method for modifying PTFE using the modified perfluorinated modifier includes the following steps: STEP101: Provide a perfluorinated modifier and octafluorocyclobutane or functionalized fullerene, then mix the octafluorocyclobutane or functionalized fullerene with the perfluorinated modifier thoroughly and heat to above 150 degrees Celsius to obtain the modified perfluorinated modifier. STEP102: Provide a polymerization reactor, and add solvent, emulsifier and initiator to the polymerization reactor to perform displacement deoxygenation treatment on the reactor, then heat up and introduce the PTFE; STEP103: Introduce a first-stage modified perfluorinated modifier while introducing the PTFE; STEP104: When the polytetrafluoroethylene has reacted to 30%-45% of the total amount, add the remaining perfluorinated modifier and some emulsifier to the reactor. STEP105: Directly add all of the PTFE to terminate the reaction, thereby forming the modified PTFE.
[0010] Furthermore, the solvent is deionized water, the emulsifier is ammonium perfluorooctanoate, and the initiator is ammonium persulfate or potassium persulfate.
[0011] Furthermore, the metal is lead powder or bronze powder.
[0012] Furthermore, the metal oxide is an oxide.
[0013] A method for fabricating a laser-welded bushing for use in an automotive oil pump includes the following steps: STEP201: Provide a modified perfluorinated modifier for modifying PTFE and PTFE, and modify the PTFE using the modified perfluorinated modifier; STEP 102: Provide raw materials for preparing the self-lubricating layer, wherein the raw materials for preparing the self-lubricating layer consist of modified PTFE, metal or metal oxide, carbon fiber, silica, graphite, and glass fiber. By weight percentage, the content of the modified PTFE is 40%–75%, the content of the carbon fiber is 10%–20%, the content of the silica is 2%–5%, the content of the graphite is 5%–15%, the content of the glass fiber is 5%–25%, and the content of the metal or metal oxide is 2%–40%. STEP103: Mix the modified PTFE, metal or metal oxide, carbon fiber, silica, graphite, and glass fiber to form a mixture; STEP104: Provide a substrate layer, the substrate layer being made of a metallic material; STEP105: The mixture is laid on the substrate layer and sintered under high temperature and high pressure to obtain the composite material. STEP106: Use the composite material to roll and form a sleeve and gasket; STEP107: Provide a laser welding machine to laser weld the sleeve and gasket together to produce the laser-welded bushing used in automotive oil pumps.
[0014] Furthermore, the metal is lead powder or bronze powder.
[0015] Compared with existing technologies, the laser-welded bushing for automotive oil pumps provided by this invention uses laser welding to weld the sleeve and gasket, thereby ensuring both the strength and weld precision between the sleeve and gasket, thus meeting the matching clearance precision requirements between the oil pump plunger and bushing. Both the sleeve and gasket are made of a composite material consisting of a substrate layer and a self-lubricating layer. To prevent the high temperatures generated by laser welding from damaging the self-lubricating layer, causing deformation or loss of lubrication, the self-lubricating layer is made of modified PTFE, metals or metal oxides, carbon fibers, silica, graphite, and glass fibers. The metals and metal oxides enable rapid heat conduction, preventing heat concentration in the welding area and achieving rapid cooling. The glass fibers, as a rigid reinforcing phase, maintain the material's structural dimensions during welding, preventing excessive collapse of the melt under hot pressure. Simultaneously, the addition of carbon fibers and silica nanoparticles significantly improves the material's compressive strength and hardness. This allows the welded joint to withstand higher mechanical loads after cooling and solidification, effectively overcoming the defects of pure PTFE welded parts, such as easy deformation and poor creep resistance. Since the addition of glass fiber, silica, and metals and metal oxides reduces the lubrication performance of PTFE, the addition of graphite and carbon fiber, which can transfer to the mating surfaces during friction to form a dense solid lubrication transfer film, provides an extremely low coefficient of friction. This compensates for the reduced lubrication performance of PTFE, allowing the laser-welded bushing to maintain excellent wear resistance and fatigue resistance even under long-term oil-free lubrication conditions. Simultaneously, the high temperature during laser welding prevents the self-lubricating layer from being damaged, thereby improving product yield. Attached Figure Description
[0016] Figure 1 This is a schematic diagram of a laser-welded bushing for use in an automotive oil pump, provided by the present invention.
[0017] Figure 2 For preparation Figure 1 A schematic diagram of the composite material structure of the laser-welded bushing.
[0018] Figure 3 For preparation Figure 1 The flowchart of the laser welding bushing. Detailed Implementation
[0019] The following provides a more detailed description of specific embodiments of the present invention. It should be understood that the description of the embodiments of the present invention herein is not intended to limit the scope of protection of the present invention.
[0020] like Figure 1The diagram shows a schematic representation of a laser-welded bushing for an automotive oil pump, provided by the present invention. The laser-welded bushing for the automotive oil pump includes a sleeve 10 and a gasket 20 welded to one axial end of the sleeve 10. The sleeve 10 and the gasket 20 are made of the same composite material. Specifically, the sleeve 10 is rolled from the composite material, while the gasket 20 is punched from a single piece of composite material. The sleeve 10 and the gasket 20 are then laser-welded together to form the bushing. Figure 2 As shown, the composite material is formed by a substrate layer 11 and a self-lubricating layer 12 disposed on the substrate layer 11.
[0021] The substrate layer can be made of a metallic material, primarily serving a load-bearing function. Therefore, this metallic material can be a copper alloy, steel plate, etc. In this embodiment, the metallic material is made of a copper alloy, which can be tin bronze, lead bronze, aluminum bronze, or other special copper alloys. Tin bronze possesses high strength, excellent wear resistance, and corrosion resistance, with grades such as ZCuSn10P1 (10-1 tin bronze) and ZCuSn5Pb5Zn5 (5-5-5 tin bronze). Lead bronze contains lead as soft particles uniformly distributed on the copper matrix, forming a natural self-lubricating structure, with grades such as ZCuPb10Sn10 (10-10 lead bronze) and ZCuPb15Sn8 (15-8 lead bronze). Aluminum bronze typically has higher strength, hardness, and wear resistance than tin bronze, making it particularly suitable for harsh working conditions, with grades such as ZCuAl10Fe3 (10-3 aluminum bronze) and ZCuAl9Fe4Ni4Mn2 (9-4-4-2 aluminum bronze). The copper alloy can also be brass or beryllium copper. In this embodiment, the copper alloy is tin bronze, where tin-lead particles can form a solid lubricating film during friction, significantly reducing the coefficient of friction and preventing adhesion to the journal. Furthermore, copper-based alloys have much higher compressive strength and fatigue strength than Babbitt metal, enabling them to withstand extremely high steady-state and impact loads. Most importantly, copper alloys have excellent thermal conductivity, rapidly dissipating the heat generated by friction, allowing operating temperatures up to 250°C or even higher.
[0022] The self-lubricating layer 12 should not only possess self-lubricating capabilities, but also withstand the high temperatures generated during laser welding of the sleeve 10 and gasket 20, achieving a balance between lubrication capacity and high-temperature resistance. It is composed of modified PTFE, metal or metal oxide, carbon fiber, silica, graphite, and glass fiber. By weight percentage, the modified PTFE content is 40%–75%, the carbon fiber content is 10%–20%, the silica content is 2%–5%, the graphite content is 5%–15%, the glass fiber content is 5%–25%, and the metal or metal oxide content is 2%–40%.
[0023] The purpose of modifying the PTFE is to give it higher density and better thermal stability, thereby making its molecular structure less susceptible to damage under conventional high-temperature processing. This fundamentally improves the temperature resistance of the self-lubricating layer 12, preventing damage or loss of its lubrication ability due to high temperatures during laser welding. To achieve this, the PTFE is first modified before mixing the raw materials for preparing the self-lubricating layer 12. Specifically, the PTFE is modified using a perfluorinated modifier to improve its thermal stability and creep resistance. The perfluorinated modifier (PPVE) is chemically known as perfluoropropyl vinyl ether or perfluoro-n-propyl vinyl ether. The purpose of modifying the perfluorinated modifier is to enhance the thermal stability, creep resistance, and mechanical strength of the PTFE. Therefore, octafluorocyclobutane or functionalized fullerene is added to first modify the perfluorinated modifier. Octafluorocyclobutane (C4F8) is a perfluorocycloalkanes with extremely high chemical and thermal stability. Octafluorocyclobutane can participate in electrochemical reactions or copolymerization modification, breaking the regularity of the pure PTFE molecular chain. This helps improve the material's performance stability under instantaneous high-temperature shock and reduces deformation under load. Simultaneously, during the modification process, all carbon-hydrogen bonds in the PTFE molecular structure are replaced by carbon-fluorine bonds, further enhancing the high-temperature resistance and corrosion resistance of the polymer substrate. Functionalized fullerenes, such as C60, can utilize molecular dynamics-level compatibility to increase the glass transition temperature and elastic modulus of PTFE, allowing it to maintain excellent mechanical strength at high temperatures. The method for modifying PTFE using the modified perfluorinated modifier includes the following steps: STEP101: Provide a perfluorinated modifier and octafluorocyclobutane or functionalized fullerene, then mix the octafluorocyclobutane or functionalized fullerene with the perfluorinated modifier thoroughly and heat to above 150 degrees Celsius to obtain the modified perfluorinated modifier. STEP102: Provide a polymerization reactor, and add solvent, emulsifier and initiator to the polymerization reactor to perform displacement deoxygenation treatment on the reactor, then heat up and introduce the PTFE; STEP103: Introduce a first-stage modified perfluorinated modifier while introducing the PTFE; STEP104: When the polytetrafluoroethylene has reacted to 30% to 45% of the total amount, add the remaining perfluorinated modifier and some emulsifier to the reactor. STEP105: Directly add all of the PTFE to terminate the reaction, thereby forming the modified PTFE.
[0024] In STEP101, the solvent can be deionized water to dissolve the PTFE, and the emulsifier can be ammonium perfluorooctanoate (PFOA), which stabilizes the generated PTFE particles and prevents them from agglomerating. The initiator can be ammonium persulfate (APS) or potassium persulfate (KPS), which decomposes to generate sulfate radicals. These radicals can open the carbon-carbon double bonds, thereby initiating a chain addition polymerization reaction. By adjusting the type and amount of initiator, the polymerization rate and the molecular weight of the polymer can be precisely controlled.
[0025] In STEP 103 and 104, because the perfluorinated modifier acts as a comonomer, its main function is to disrupt the regularity of the PTFE molecular chain, reduce crystallinity, and increase the amorphous content, thereby improving the material's thermal stability and creep resistance. Therefore, its phased introduction allows for precise control of molecular weight and particle integration. Since modified PTFE typically requires a lower molecular weight, this facilitates better particle integration during subsequent processing. By adding modifiers in stages, the molecular weight distribution of the polymer can be precisely controlled. Furthermore, adding modifiers at different stages of polymerization can create "core-shell" particle morphologies with differentiated modification levels. For example, introducing modifiers or functional monomers in the later stages of polymerization can form a low-molecular-weight or modified-group-rich shell layer on the outside of a high-molecular-weight PTFE core. This structure not only reduces interparticle friction and improves extrusion stability but also imparts better surface processing properties while maintaining excellent core thermal stability.
[0026] Chemical modification by adding modified perfluorinated modifiers is equivalent to "upgrading" the molecular structure of PTFE. This modified material can significantly reduce deformation under load when facing high-temperature shock, maintaining extremely high thermal stability and a smoother surface.
[0027] The metal or metal oxide is used to significantly improve the thermal conductivity, cold flow resistance, and stabilize the coefficient of friction of the composite material. Therefore, the metal or metal oxide should have both high thermal conductivity and low coefficient of friction; thus, it can be lead powder, lead oxide, or bronze powder, etc. In this embodiment, the metal or metal oxide is bronze powder. Due to the presence of the metal or metal oxide, the high temperature generated during laser welding can be promptly directed to the surface of the self-lubricating layer 12 for heat dissipation, preventing damage to the modified PTFE from high temperatures. However, the weight percentage of the metal or metal oxide must be controlled between 2% and 40%. Below 2%, it cannot provide sufficient thermal conductivity; above 40%, it will reduce the amount of modified PTFE used, leading to a decrease in the self-lubricating performance of the composite material.
[0028] The carbon fiber is used to improve the mechanical strength, thermal conductivity, and wear resistance of the composite material. Adding carbon fiber is a common method for improving the mechanical strength and wear resistance of self-lubricating materials. The carbon fiber content should be controlled between 10% and 20%. If the carbon fiber content is too low (below 10%), although the material can maintain good flexibility and an extremely low coefficient of friction, it cannot form a sufficiently dense reinforcing network. This results in insufficient creep resistance and wear resistance under high loads or high temperatures, making it difficult to meet the requirements of oil pump bushings. If the content is greater than 20%, although it can further improve the rigidity and heat resistance of the material, the tensile strength of the composite material will decrease as the carbon fiber content increases further. Excessive carbon fiber will also cause the coefficient of friction to increase instead of decrease, weakening the lubrication effect of the material. Furthermore, excessive carbon fiber content will lead to poor compatibility with the PTFE matrix, making the material brittle and difficult to process. It will also easily cause carbon fiber breakage and peeling from the matrix during friction, thus exacerbating wear.
[0029] The addition of silica aims to achieve high-temperature resistance and resistance to thermal aging, specifically to prevent PTFE from degrading near its melting point or thermal decomposition threshold. Therefore, a high-temperature resistant substance is introduced into the composition to enhance the thermal stability of its molecular structure. Both silica and graphite added in this invention possess the aforementioned functions. Of course, in addition to enhancing thermal stability, silica also improves the mechanical properties and tribological properties of the composite material, but the addition amount needs to be controlled between 2% and 5%. If the content is below 2%, the filler quantity is insufficient to form an effective rigid support network in the PTFE matrix, thus the improvement effect on the material's thermal stability, wear resistance, and creep resistance is insufficient. However, if the content is greater than 5%, although it can further improve the material's rigidity and heat resistance, exceeding the reasonable upper limit of 5% results in a significant difference in surface properties between the inorganic silica and the organic PTFE matrix, and without good interface modification, the interfacial bonding deteriorates, meaning silica particles will fall off, forming wear points and actually increasing the coefficient of friction.
[0030] As described above, graphite enhances the thermal stability of the molecular structure. When incorporated into PTFE, it improves the overall heat resistance limit of the composite material, preventing premature softening or decomposition of the matrix at high temperatures. Furthermore, because graphite can withstand extremely high temperatures, it stabilizes the structure of the modified PTFE at high temperatures. Additionally, as a solid lubricant, graphite forms a transfer film on the friction surface, thereby reducing the coefficient of friction, stabilizing friction performance, and lowering the wear rate. The graphite content should be controlled between 5% and 10%. If it is below 5%, although the composite material can maintain the chemical inertness and low coefficient of friction of PTFE, the filler quantity is insufficient to form a continuous and dense transfer film on the friction surface. This cannot overcome the increase in the coefficient of friction caused by the addition of metal and metal oxide powders, glass fibers, and silica. In particular, the inability to form a transfer film exposes the metal and metal oxide powders, glass fibers, and silica, leading to an exponential decrease in wear resistance. Therefore, this method can fundamentally solve the shortcomings caused by the addition of metal and metal oxide powders, glass fibers, and silica. At the same time, if too much graphite is added, such as more than 10%, it will weaken the overall mechanical strength of the composite material, making the material prone to plastic deformation under heavy loads.
[0031] The primary purpose of adding glass fibers is to improve compressive strength, creep resistance, and dimensional stability. During laser welding, temperatures can reach between 1150°C and 1300°C, which is unbearable for the modified PTFE. Therefore, the addition of glass fibers ensures a melting temperature of at least 1400°C. These glass fibers form a framework, allowing the molten modified PTFE to fill the spaces between the glass fibers and carbon fibers through capillary action, preventing creep and thus ensuring the stability of the self-lubricating layer 12. Furthermore, the high temperatures generated during oil pump operation also contribute to maintaining the compressive strength of the self-lubricating layer 12. The glass fiber content should be controlled between 5% and 25%. If the glass fiber content is below 5%, it will be insufficient to form an effective rigid support network within the modified PTFE matrix during laser welding. In this case, the composite material will still retain the disadvantages of the modified PTFE, such as poor creep resistance, easy wear, and susceptibility to cold flow, and will not be able to withstand the high temperatures associated with laser welding. If the glass fiber content is higher than 25%, although it can further improve the rigidity, compressive strength and creep resistance of the material, excessive glass fiber will make the composite material exhibit obvious brittle characteristics. At the same time, during the friction process, high glass fiber particles are more likely to fall off from the matrix, which will not only leave pits on the friction surface, but also cause serious abrasive wear, resulting in a rougher friction surface and even aggravating the wear of the mating parts.
[0032] like Figure 3 As shown, the present invention also provides a method for preparing a laser-welded bushing for use in an automotive oil pump, which includes the following steps: STEP201: Provide a modified perfluorinated modifier for modifying PTFE and PTFE, and modify the PTFE using the modified perfluorinated modifier; STEP202: Provide raw materials for preparing the self-lubricating layer, wherein the raw materials for preparing the self-lubricating layer consist of modified PTFE, metal or metal oxide, carbon fiber, silica, graphite, and glass fiber. By weight percentage, the content of the modified PTFE is 40%–75%, the content of the carbon fiber is 10%–20%, the content of the silica is 2%–5%, the content of the graphite is 5%–15%, the content of the glass fiber is 5%–25%, and the content of the metal or metal oxide is 2%–40%. STEP203: Mix the modified PTFE, metal or metal oxide, carbon fiber, silica, graphite, and glass fiber to form a mixture; STEP204: Provide a substrate layer, said substrate layer being made of a metallic material; STEP205: The mixture is laid on the substrate layer and sintered under high temperature and high pressure to obtain the composite material; STEP206: Use the composite material to roll and form the sleeve 10 and the gasket 20; STEP207: Provide a laser welding machine to laser weld the sleeve 10 and the gasket 20 together to produce the laser-welded bushing used in an automotive oil pump.
[0033] Compared with existing technologies, the laser-welded bushing for automotive oil pumps provided by this invention uses laser welding to weld the sleeve 10 and the gasket 20, thereby ensuring both the strength between the sleeve 10 and the gasket 20 and the precision of the weld seam, thus meeting the matching clearance precision requirements between the oil pump plunger and the bushing. Both the sleeve 10 and the gasket 20 are made of a composite material consisting of a substrate layer 11 and a self-lubricating layer 12. To prevent the high temperatures generated by laser welding from damaging the self-lubricating layer 12, causing it to deform or lose its lubricating ability, the self-lubricating layer 12 is made of modified PTFE, metals or metal oxides, carbon fibers, silica, graphite, and glass fibers. The metals and metal oxides enable rapid heat conduction, preventing heat concentration in the welding area and achieving rapid cooling. The glass fibers, as a rigid reinforcing phase, maintain the material's structural dimensions during welding, preventing excessive collapse of the melt under hot pressure. Simultaneously, the addition of carbon fibers and silica nanoparticles significantly improves the material's compressive strength and hardness. This allows the welded joint to withstand higher mechanical loads after cooling and solidification, effectively overcoming the defects of pure PTFE welded parts, such as easy deformation and poor creep resistance. Since the addition of glass fiber, silica, and metals and metal oxides reduces the lubrication performance of PTFE, graphite and carbon fibers are added. These graphite and carbon fibers can transfer to the mating surfaces during friction, forming a dense solid lubrication transfer film that provides an extremely low coefficient of friction. This compensates for the reduced lubrication performance of PTFE, allowing the laser-welded bushing to maintain excellent wear resistance and fatigue resistance even under long-term oil-free lubrication conditions. Simultaneously, the high temperature during laser welding prevents the self-lubricating layer 12 from being damaged, thereby improving product yield.
[0034] The above are merely preferred embodiments of the present invention and are not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions or improvements within the spirit of the present invention are covered within the scope of the claims of the present invention.
Claims
1. A laser-welded bushing for use in automotive oil pumps, characterized in that: The laser-welded bushing used in automotive oil pumps comprises a sleeve and a gasket. The gasket is welded to one axial end of the sleeve using a laser welding process. Both the sleeve and the gasket are made of a composite material, which includes a substrate layer and a self-lubricating layer disposed on the substrate layer. The self-lubricating layer is composed of modified PTFE, metal or metal oxide, carbon fiber, silica, graphite, and glass fiber. By weight percentage, the modified PTFE content is 40%–75%, the carbon fiber content is 10%–20%, the silica content is 2%–5%, the graphite content is 5%–15%, the glass fiber content is 5%–25%, and the metal or metal oxide content is 2%–40%. The modified PTFE is prepared by modifying the PTFE with a modified perfluorinated modifier, which is prepared by modifying the perfluorinated modifier with octafluorocyclobutane or functionalized fullerene.
2. The laser-welded bushing for an automotive oil pump as described in claim 1, characterized in that: The substrate layer is made of a metallic material, which may be a copper alloy or a steel plate.
3. The laser-welded bushing for an automotive oil pump as described in claim 2, characterized in that: The copper alloy is one of tin bronze, lead bronze, and aluminum bronze.
4. The laser-welded bushing for an automotive oil pump as described in claim 1, characterized in that: The perchloric modifier is perfluoropropyl vinyl ether or perfluoron-propyl vinyl ether.
5. The laser-welded bushing for an automotive oil pump as described in claim 1, characterized in that: The method for modifying PTFE using a modified perfluorinated modifier includes the following steps: STEP101: Provide a perfluorinated modifier and octafluorocyclobutane or functionalized fullerene, then mix the octafluorocyclobutane or functionalized fullerene with the perfluorinated modifier thoroughly and heat to above 150 degrees Celsius to obtain the modified perfluorinated modifier. STEP102: Provide a polymerization reactor, and add solvent, emulsifier and initiator to the polymerization reactor to perform displacement deoxygenation treatment on the reactor, then heat up and introduce the PTFE; STEP103: Introduce a first-stage modified perfluorinated modifier while introducing the PTFE; STEP104: When the polytetrafluoroethylene has reacted to 30%-45% of the total amount, add the remaining perfluorinated modifier and some emulsifier to the reactor. STEP105: Directly add all of the PTFE to terminate the reaction, thereby forming the modified PTFE.
6. The laser-welded bushing for an automotive oil pump as described in claim 5, characterized in that: The solvent is deionized water, the emulsifier is ammonium perfluorooctanoate, and the initiator is ammonium persulfate or potassium persulfate.
7. The laser-welded bushing for an automotive oil pump as described in claim 4, characterized in that: The metal is lead powder or bronze powder.
8. The laser-welded bushing for an automotive oil pump as described in claim 1, characterized in that: The metal oxide is an oxide.
9. A method for manufacturing a laser-welded bushing for use in an automotive oil pump, comprising the following steps: STEP201: Provide a modified perfluorinated modifier for modifying PTFE and PTFE, and modify the PTFE using the modified perfluorinated modifier; STEP 102: Provide raw materials for preparing the self-lubricating layer, wherein the raw materials for preparing the self-lubricating layer consist of modified PTFE, metal or metal oxide, carbon fiber, silica, graphite, and glass fiber. By weight percentage, the content of the modified PTFE is 40%–75%, the content of the carbon fiber is 10%–20%, the content of the silica is 2%–5%, the content of the graphite is 5%–15%, the content of the glass fiber is 5%–25%, and the content of the metal or metal oxide is 2%–40%. STEP103: Mix the modified PTFE, metal or metal oxide, carbon fiber, silica, graphite, and glass fiber to form a mixture; STEP104: Provide a substrate layer, the substrate layer being made of a metallic material; STEP105: The mixture is laid on the substrate layer and sintered under high temperature and high pressure to obtain the composite material. STEP106: Use the composite material to roll and form a sleeve and gasket; STEP107: Provide a laser welding machine to laser weld the sleeve and gasket together to produce the laser-welded bushing used in automotive oil pumps.
10. The preparation method according to claim 9, characterized in that: The metal is lead powder or bronze powder.
Citation Information
Patent Citations
Device for advancing sheets or batches of sheets
EP0103104A2